Pengaruh Pertumbuhan Penjualan, Intensitas Modal dan Intensitas Persediaan terhadap Penghindaran Pajak pada Perusahaan Sektor Aneka Industri yang Terdaftar di BEI Tahun 2017-2022 - Anastasya, Elda Permata; Priantilianingtiasari, Ruly (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study was to analyze and determine 1) sales growth influence on tax avoidance. 2) Capital intensity influence on tax avoidance. 3) Inventory intensity affects tax avoidance. 4) Sales growth, capital intensity, and inventory intensity influence tax avoidance. The population used in this study were 56 companies in various industrial sectors listed on the IDX for the period 2017 - 2022. The number of research samples obtained was 12 companies with a total sample of 72 companies. The sampling technique used in this study was purposive sampling. The data source used in this research is secondary data. Data analysis using panel data analysis with Eviews. The results showed that 1) sales growth affects tax avoidance. 2) Capital intensity has no effect on tax avoidance. 3) Inventory intensity has no effect on tax avoidance. 4) Sales growth, capital intensity and inventory intensity simultaneously affect tax avoidance Keywords: Tax Avoidance, Sales Growth, Capital Intensity, Inventory Intensity